Field calibration of weirs using unsteady flow techniques - Silvestre, Patricio Elegado; Ackermann, Norbert L.; Shi-igai, Hiroyoshi; Petersen, Jens L.; Government of the United Kingdom (Bangkok : Asian Institute of Technology, 1974)
A theoretical study on the effect of translatory waves on unsteady flow weir calibration was undertaken in an attempt to develop a criteria for the use of unsteady flow or falling head weir calibration. The translatory negative waves which occur during the calibration were assumed to be steep-fronted in an effort to simplify the solution. This assumption, however, was found out to give results which arc not accurate enough for the establishment of the criteria .
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology, 1974
Keywords: Weirs; Fluid dynamics